Insights into the evolution of pathogenicity of Escherichia coli from genomic analysis of intestinal E. coli of Marmota himalayana in Qinghai–Tibet plateau of China - Shan Lu; Dong Jin; Shusheng Wu; Jing Yang; Ruiting Lan; Xiangning Bai; Sha Liu; Qiong Meng; Xuejiao Yuan; Juan Zhou; Ji Pu; Qiang Chen; et al. (Emerging Microbes and Infections, 2016)
Escherichia coli is both of a widespread harmless gut commensal and a versatile pathogen of humans. Domestic animals are a well-known reservoir for pathogenic E. coli. However, studies of E. coli populations from wild animals that have been separated from human activities had been very limited. Here we obtained 580 isolates from intestinal contents of 116 wild Marmot Marmota himalayana from Qinghai–Tibet plateau, China, with five isolates per animal. We selected 125 (hereinafter referred to as strains) from the 580 isolates for genome sequencing, based on unique pulse field gel electrophoresis patterns and at least one isolate per animal. Whole genome sequence analysis revealed that all 125 strains carried at least one and the majority (79.2%) carried multiple virulence genes based on the analysis of 22 selected virulence genes. In particular, the majority of the strains carried virulence genes from different pathovars as potential 'hybrid pathogens'. The alleles of eight virulence genes from the Marmot E. coli were found to have diverged earlier than all known alleles from human and other animal E. coli. Phylogenetic analysis of the 125 Marmot E. coli genomes and 355 genomes selected from 1622 human and other E. coli strains identified two new phylogroups, G and H, both of which diverged earlier than the other phylogroups. Eight of the 12 well-known pathogenic E. coli lineages were found to share a most recent common ancestor with one or more Marmot E. coli strains. Our results suggested that the intestinal E. coli of the Marmots contained a diverse virulence gene pool and is potentially pathogenic to humans. These findings provided a new understanding of the evolutionary origin of pathogenic E. coli.Emerging Microbes & Infections (2016) 5, e122; doi:10.1038/emi.2016.122; published online 7 December 2016